Post Broadcast Society and Intermedia Agenda Setting: An Analysis of India’s Major Newspapers and SNS - Guha, Dr. Silajit; Bhattacharjee, Nilotpal (IJRDO - Journal of Social Science and Humanities Research, 2017)
The avowed practice of assessing public mood and setting the tone of public discussion through newspaper or television prime hours got disrupted with the intrusion of social media into media scape in the first decade of 21 st century. The adoption of social media for expression of collective anger unsettled the applecart of autocratic rule in the middle east and the ripples of Jasmine revolution cascaded into anti-corruption movement in New Delhi in 2011. It has been quite a tempestuous decade for social media in terms of consolidating its grip on collective imagination. In the west, it has already become a norm to relegate conventional media to the backburner, yielding the temple of public discussion to social media. It was important to explore how far the SNS have taken hold of public imagination in Indian non-metro urban locations. This work sought to fathom the capability of SNS vis-à-vis newspapers in terms of agenda setting in the peripheral locations of India’s northeast. It was found that at least in the context of Indian small towns, social networking sites like Facebook is yet to evolve as the match winner in terms of setting the agenda of public discussion.